Tingkat Kompetensi Teknis Petani dalam Berusahatani Singkong (Kasus Kelompok Mekar Tani Desa Cibanteng Kecamatan Ciampea Kabupaten Bogor - Ture Simamora; Renfred Luik (Fakultas Pertanian, Universitas Timor, 2019)
Competence is a person's characteristic related to the best performance in a particular job. Farmers' competence is not the same between one farmer and other farmers, this is related to the support characteristics possessed by farmers. The Mekar Tani group in Cibanteng Village still operates cassava in the traditional way. The research aims to analyze the characteristics of cassava farmers, analyze the technical competence of cassava farming, and analyze the relationship between the characteristics of farmers with technical competence. The results showed as many as 63.30 percent of cassava farmers were old, 53.30 percent had low formal education, 60 percent of farmers had low cassava farming experience, 80 percent of farmers had narrow land area, 93.33 percent of farmers had high motivation in farming, and 36.67 percent support for facilities and high production infrastructure. Farmers' technical competency is low in cassava farming. Technical competence of farmers in cassava farming. Farmers' knowledge is high in farming. The attitude of farmers is high in cassava farming. Low skills of farmers in cassava farming. Characteristics of cassava farmers that show a real relationship with technical competence in cassava farming include farming experience, land area and the support of production infrastructure. Thus to develop the technical competence of farmers it is necessary to increase extension services in the field of cassava agriculture.